Pembelajaran Berbasis Konstruktivisme Menggunakan Media Animasi dengan Kerangka Kerja TPCK dan Gaya Belajar Terhadap Prestasi Belajar Siswa - Handy Darmawan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2016)
The purpose of this study was to determine the influence of constructivism based learning using media animation with TPCK framework and learning styles on student achievement. This study used an experimental method with a true experimental design. The population of this research is all class XI student of SMK 1 Dedai the academic year 2014/2015 Prodi computer technology and a network of four classes. Samples were taken from a population of 2 classes. Data collection techniques used in this study is the test method to measure student achievement, to measure learning style questionnaire and observation sheet as to measure learning outcomes affective and psychomotor student. The results showed; 1) learning style profiles of class XI student of SMK 1 Dedai; 2) there is influence of constructivism based learning using animation media on student achievement, (3) there is no influence of learning styles on student achievement, (4) there is the influence of animation media usage and learning styles on student achievement. Keyword: Constructivism, TPCK, Animation Learning, Learning Style.